2014
DOI: 10.3174/ajnr.a3909
|View full text |Cite
|
Sign up to set email alerts
|

High-Resolution MRI Vessel Wall Imaging: Spatial and Temporal Patterns of Reversible Cerebral Vasoconstriction Syndrome and Central Nervous System Vasculitis

Abstract: BACKGROUND AND PURPOSE: High-resolution MR imaging is an emerging tool for evaluating intracranial artery disease. It has an advantage of defining vessel wall characteristics of intracranial vascular diseases. We investigated high-resolution MR imaging arterial wall characteristics of CNS vasculitis and reversible cerebral vasoconstriction syndrome to determine wall pattern changes during a follow-up period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
185
4
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 236 publications
(196 citation statements)
references
References 27 publications
6
185
4
1
Order By: Relevance
“…32 Both disorders result in arterial wall thickening, but the vessel wall in RCVS is typically nonenhancing (or mildly enhancing) compared with the typical intense wall enhancement in active vasculitis. 29,32,33 Arterial wall thickening with a lack of wall enhancement is consistent with the pathology of transient vasoconstriction. In vasospastic arteries, smoothmuscle cells shorten in length with increased overlap among cells, resulting in nearly a 500% increase in wall thickness for a 60% luminal narrowing.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…32 Both disorders result in arterial wall thickening, but the vessel wall in RCVS is typically nonenhancing (or mildly enhancing) compared with the typical intense wall enhancement in active vasculitis. 29,32,33 Arterial wall thickening with a lack of wall enhancement is consistent with the pathology of transient vasoconstriction. In vasospastic arteries, smoothmuscle cells shorten in length with increased overlap among cells, resulting in nearly a 500% increase in wall thickness for a 60% luminal narrowing.…”
mentioning
confidence: 68%
“…A small number of published cases 29 and the broader experience of the study group suggest that there may be a discordance between intracranial VW-MR imaging findings and the clinical impression of vasculitis disease activity. This is consistent with extracranial VW-MR imaging observations.…”
Section: To Assess Vasculitis Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, some studies have suggested that arterial wall imaging may enable differentiation between RCVS and PCNSV with specific imaging patterns. 24,25 Although the present study suggests that demonstration of multifocal segmental stenosis of cerebral arteries on 3D-TOF-MRA may be sufficient to strengthen the diagnostic suspicion of PCNSV, DSA may also be necessary to add precise lesional mapping in the distal vasculature and rule out mimics. Finally, we performed per-patient and per-segment analyses.…”
mentioning
confidence: 97%
“…Emerging studies have suggested that HRMRI is reliable for detecting intracranial artery wall lesions, consistent with histology findings (7)(8)(9)(10)(11). On HRMRI, eccentric stenosis is suggestive of atherosclerosis while concentric stenosis is suggestive of non-atherosclerotic diseases, although overlap may occasionally exist (3,8,(12)(13)(14). In this study, using HRMRI, we sought to observe the vessel wall properties of intracranial stenosis in Chinese young patients and investigate the underlying etiology.…”
Section: Introductionmentioning
confidence: 99%